BODIPY-based iridium and ruthenium complexes: Synthesis, photophysical, and photochemical properties - Cabir, Beyza; Cetindere, Seda (Wiley-V C H Verlag Gmbh, 2024)
The design, synthesis, and characterization of novel BODPY-based iridium and ruthenium complexes were reported. The structures of new compounds were fully characterized by FT-IR, MALDI-TOF mass analysis, elemental analysis, H-1, and F-19 NMR spectroscopies. Precursor BODIPY was characterized by single-crystal x-ray diffraction technique for the first time. Photophysical properties including absorption and emission profiles and lifetimes were investigated via UV-vis absorption and emission spectroscopy. Photochemical properties were investigated via direct method, and the singlet oxygen production capabilities of new complexes were determined by NIR phosphorescence methods. BODIPY-based new complexes were efficient at producing O-1(2). Besides, both complexes showed more remarkable photosensitization ability than some commonly used photosensitizer based on BODIPY derivatives. This study points out that novel complexes are effective O-1(2) photosensitizers that might be used for different application areas like photodynamic therapy.
Keywords: BODIPY; iridium; PDT; photochemical property; photophysical property; ruthenium; singlet oxygen